Effect of Rho-kinase Inhibitor, Y27632, on Porcine Corneal Endothelial Cell Culture, Inflammation and Immune Regulation. (2nd September 2016) - Lee, Whayoung; Miyagawa, Yuko; Long, Cassandra; Zhang, Matthew; Cooper, David K. C.; Hara, Hidetaka
Abstract: Purpose : To investigate the effect of the Rho-kinase inhibitor, Y27632, on pig corneal endothelial cell (pCEC) culture, and on inflammation and immune regulation of the responses of human cells to pCECs. Methods : pCECs were cultured with/without Y27632 to assess cell proliferation and in vitro wound healing assay. The level of MCP-1 and VEGF in pCECs stimulated with human TNF-α were measured. Proliferation of human PBMCs stimulated with pCECs, and cytokine production in human T cells, and monocyte migration after stimulation were investigated. Results : Y27632 promoted pCEC proliferation, prevented pCEC death, and enhanced in vitro wound healing. After stimulation, there were significantly lower levels of MCP-1 and VEGF measured in pCECs cultured with Y27632, and significantly reduced human PBMC proliferation, cytokine production, and monocyte migration. Conclusions : The application of the Rho-kinase inhibitor will be beneficial when culturing pCECs, and may provide a novel therapy to reduce inflammation after corneal xenotransplantation.